2016
DOI: 10.1111/hdi.12417
|View full text |Cite
|
Sign up to set email alerts
|

Vascular refilling is independent of volume overload in hemodialysis with moderate ultrafiltration requirements

Abstract: Introduction Blood volume changes and vascular refilling during hemodialysis (HD) and ultrafiltration (UF) have been assumed to depend on volume overload (Vo ). It was the aim to study the magnitude of vascular refilling in stable HD patients with moderate volume expansion in everyday dialysis using novel technical approaches. Methods Patients were studied during routine dialysis and UF based on clinical dry weight assessment. Pre-dialysis Vo was independently measured by bioimpedance spectroscopy. Vascular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 34 publications
3
42
1
1
Order By: Relevance
“…In that previous study the refilling fraction appeared to be relatively uniform amounting to about 70% of the total UF volume and was independent of the fluid overload [12]. This finding was different from studies where vascular refilling increased especially with severe volume expansion [4,16,17], but it is in line with the refilling fraction of 74 ± 9% identified in nine dialysis patients using a mathematical model [18].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In that previous study the refilling fraction appeared to be relatively uniform amounting to about 70% of the total UF volume and was independent of the fluid overload [12]. This finding was different from studies where vascular refilling increased especially with severe volume expansion [4,16,17], but it is in line with the refilling fraction of 74 ± 9% identified in nine dialysis patients using a mathematical model [18].…”
Section: Discussionmentioning
confidence: 60%
“…In a previous study, we found that the refilling volume linearly increased with UF volume in stable chronic HD patients with moderate UF requirements [12]. In that previous study the refilling fraction appeared to be relatively uniform amounting to about 70% of the total UF volume and was independent of the fluid overload [12].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It is known that higher ultrafiltration rates/volumes are associated with larger intradialytic decreases in BP [24]. While there is a strong negative correlation between ultrafiltration rate/volume and intravascular blood volume, there is a strong positive correlation between the post-HD volume overload and intravascular blood volume [32]. Importantly, the association between IBPS and ECW/body weight that we found was independent of the ultrafiltration rate.…”
Section: Discussionmentioning
confidence: 46%
“…In the present study, BW gain and BW/DW in HD were generally larger than in ol-HDF, which might have facilitated the refilling during HD sessions and so underestimated IPVD in HD. However, because fluid excess was reported to not influence refilling [19], the possible difference in fluid excess between the modes would not have significantly influenced IPVD.…”
Section: Discussionmentioning
confidence: 99%